The Need for Use of Information Technologies in Transport Logistics - Melikoziev Boburmirzo Ilkhomjon oglu (Zien Journals, 2022)
This article discusses the main stages of transport logistics, the benefits of using information technology in logistics, the use of modern information technology in the logistics of large foreign and domestic transport companies and the introduction of enterprise resource planning systems.
Keywords: Transport; transport logistics; logistics centers; virtual information space